Lateralization of attention in adults with ADHD: Evidence of pseudoneglect. Issue 1 (2020) - Helfer, Bartosz; Maltezos, Stefanos; Liddle, Elizabeth; Kuntsi, Jonna; Asherson, Philip
Abstract: Background: We investigated whether adults with attention-deficit/hyperactivity disorder (ADHD) show pseudoneglect—preferential allocation of attention to the left visual field (LVF) and a resulting slowing of mean reaction times (MRTs) in the right visual field (RVF), characteristic of neurotypical (NT) individuals —and whether lateralization of attention is modulated by presentation speed and incentives. Method: Fast Task, a four-choice reaction-time task where stimuli were presented in LVF or RVF, was used to investigate differences in MRT and reaction time variability (RTV) in adults with ADHD ( n = 43) and NT adults ( n = 46) between a slow/no-incentive and fast/incentive condition. In the lateralization analyses, pseudoneglect was assessed based on MRT, which was calculated separately for the LVF and RVF for each condition and each study participant. Results: Adults with ADHD had overall slower MRT and increased RTV relative to NT. MRT and RTV improved under the fast/incentive condition. Both groups showed RVF-slowing with no between-group or between-conditions differences in RVF-slowing. Conclusion: Adults with ADHD exhibited pseudoneglect, a NT pattern of lateralization of attention, which was not attenuated by presentation speed and incentives.